Corrupción y Crecimiento Económico en los Países de América Latina, período 2002- 2016 - Yambay Calderón, Tania Monserrath (2019)
The aim is to identify the relationship between corruption and economic growth in Latin American countries (17 countries), period 2002 to 2016. Through generalized least squares, the relationship between the corruption perception index and the gross domestic product is estimated per capita. Foreign direc investment and gross fixed capital formation are also using as control variables. On the other hand, there is an estimation of autoregressive vectors where it is possible to identify a significant relationship between the variables and the short term. Which analysis is not carried out by periods buy by countries that nested are. A positive relationship between corruption and economic growth for Latin American countries is concluding.